1981
DOI: 10.1016/s0006-3495(81)84821-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel kinetics in the sodium conductance system predicted by the aggregation model of channel gating

Abstract: Special voltage-clamp pulse protocols are given that make differential predictions for the kinetics of models based on a simple sequential, simple cyclic, and an aggregation scheme. Detailed kinetic time-courses for the discriminating pulse protocols are numerically derived from the differential equation system that describes the aggregation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This predicts that latency to Na+ channel opening, and therefore the decay rate of INa, might be different after brief depolarizations or after rapid pulse trains when channels might accumulate in this putative state and if this state is near the open state. Such a mechanism may account for the more rapid decay found in the INa traces after brief depolarizations (e.g., Frankenhaeuser, 1963;Baumann, 1981) in nerve or for the traces at the end of a rapid pulse train as compared with the first pulse in heart (Makielski and Falleroni, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This predicts that latency to Na+ channel opening, and therefore the decay rate of INa, might be different after brief depolarizations or after rapid pulse trains when channels might accumulate in this putative state and if this state is near the open state. Such a mechanism may account for the more rapid decay found in the INa traces after brief depolarizations (e.g., Frankenhaeuser, 1963;Baumann, 1981) in nerve or for the traces at the end of a rapid pulse train as compared with the first pulse in heart (Makielski and Falleroni, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A possible answer to the first question is that the models tested in the Appendix were primarily designed to reproduce the time development of membrane conductance (c.f. Hodgkin-Huxley, 1952;and Baumann, 1981). Those kinetic schemes may fail when pressed beyond that original purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic equations of gating models that contain mathematical features not found in the Hodgkin-Huxley equations were also integrated in dynamic steady states and the simulated gating currents subjected to harmonic analyses. These models included aggregation gating (Baumann, 1981) and an excited state model (Jakobsson, 1978). The aggregation kinetic equations contain nonlinear terms (i.e., products of dependent variables of the form x,x;) and the excited state model contains one rate constant whose value depends on the rate of change of the membrane potential.…”
Section: Other Kinetic Modelsmentioning
confidence: 99%
“…Initial condition-induced changes have been reported for the time constant of the macroscopic inactivation by Chandler and Meves (1970) and for the time course of the tail currents by Goldman and Hahin (1978) and by Sigworth (1981). The change of the time constants with the initial conditions can be explained either by the aggregation model of Baumann (1981Baumann ( , 1983, or by assuming that the calculated time constants are the mean of two or more time constants, whose weight changes with the initial conditions (see Goldman & Hahin, 1978 Sigworth (1981). He showed that in the node of Ranvier channels which open late during a depolarization stay open longer.…”
Section: R~ci~-mentioning
confidence: 99%